Leveraging Post-Mining Assets for Renewable Energy: A Retscreen Techno-Economic and Carbon Credit Analysis of PT Bukit Asam's Solar PV Project - Rahmaana, Harindiarto; Hakam, Dzikri Firmansyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
The increasing global demand for clean energy and decarbonization is driving coal-dependent companies to transform their business strategies. PT Bukit Asam Tbk (PTBA), a major coal-mining enterprise in Indonesia, is pursuing renewable energy projects that support the country’s energy transition agenda. This research examines the economic feasibility of establishing a large-scale photovoltaic (PV) power plant on PTBA’s reclaimed mining land in Muara Enim, South Sumatra. Using a quantitative approach, the study applies RETScreen Expert to model technical performance, assess financial outcomes, and estimate reductions in greenhouse gas (GHG) emissions. Project feasibility is measured through Net Present Value (NPV), Internal Rate of Return (IRR), Levelized Cost of Electricity (LCOE), Payback Period (PBP), cost–benefit analysis, and potential carbon credits from GHG mitigation. Data on climate conditions, financial parameters, and technical inputs were collected from literature, secondary datasets, and regulatory sources. Results show that the project is financially sound across different scenarios: in the baseline case, it achieves an NPV of USD 604,946, a pre-tax equity IRR of 14%, a payback period of 8.1 years, and a Benefit–Cost Ratio (BCR) of 1.3; in the optimal case, with carbon credits included, the project reaches an NPV of USD 6,104,817, a pre-tax equity IRR of 43%, a 5-year payback, and a BCR of 3.5. RETScreen demonstrates strong capability in scenario modeling, identifying critical design factors, and assessing project suitability for implementation.